Solve each system of equations by ELIMINATION. Clearly identify your solution. \( \begin{array}{ll}\text { 7. }\left\{\begin{array}{l}x-y=-10 \\ x-6 y=-25\end{array}\right. & \text { 8. } \\ 2 x+2 y=28 \\ 8 x-2 y=22\end{array} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve these systems of equations by elimination, let's tackle each system one by one. **For system 7:** \[ \begin{cases} x - y = -10 \quad (1) \\ x - 6y = -25 \quad (2) \end{cases} \] We'll eliminate \(x\). First, we can multiply equation (1) by 6: \[ 6(x - y) = 6(-10) \\ 6x - 6y = -60 \quad \text{(3)} \] Now we subtract equation (2) from equation (3): \[ (6x - 6y) - (x - 6y) = -60 - (-25) \\ 6x - x = -60 + 25 \\ 5x = -35 \\ x = -7 \] Substituting \(x = -7\) back into equation (1) to find \(y\): \[ -7 - y = -10 \\ -y = -3 \\ y = 3 \] Thus, the solution for system 7 is \( (x, y) = (-7, 3) \). --- **For system 8:** \[ \begin{cases} 2x + 2y = 28 \quad (1) \\ 8x - 2y = 22 \quad (2) \end{cases} \] Let’s simplify equation (1) by dividing everything by 2: \[ x + y = 14 \quad (3) \] Now, we can express \(y\) in terms of \(x\): \[ y = 14 - x \quad (4) \] Next, substitute equation (4) into equation (2): \[ 8x - 2(14 - x) = 22 \\ 8x - 28 + 2x = 22 \\ 10x - 28 = 22 \\ 10x = 50 \\ x = 5 \] Now substitute \(x = 5\) back into equation (4): \[ y = 14 - 5 = 9 \] Thus, the solution for system 8 is \( (x, y) = (5, 9) \). **Final Answers:** - System 7: \( (x, y) = (-7, 3) \) - System 8: \( (x, y) = (5, 9) \)